SRAD: Smart Routing Algorithm Design for Supporting IoT Network Architecture - MONSAKUL, ANNOP (International Journal of Communication Networks and Information Security (IJCNIS), 2022)
The smart things require applications and services such as high-speed wireless, high-definition IP video cameras, and high-bandwidth connectivity. Therefore, Fog computing is responsible reducing the amount of data sent to the cloud with smart router over the core network. The IP/MPLS network design to support unicast traffic under delay constraints is a severe problem. To realize such design, especially for communication networks that can be represented by M/M/1 model, this paper develops an algorithm based on Mesh Network Topological Optimization and Routing (MENTOR)-II was called “Smart MENTOR-II”. The simulation results show that, in almost all test cases, the proposed algorithm yields lower installation cost and delay constraints than the ordinary MENTOR-II.